The early intervention message: perspectives of parents of children with autism spectrum disorder. (28th November 2016) - Edwards, A.; Brebner, C.; McCormack, P.; MacDougall, C.
Abstract: Background: There is strong evidence that early intervention (EI) can improve outcomes for children with autism spectrum disorder (ASD), and consequently, the importance of EI has been widely promoted to families of children with ASD. However, the perspectives of parents of children with ASD regarding the EI message have not been widely examined. Methods: This study used qualitative methods to explore parental perspectives on the EI message. Semi‐structured interviews were undertaken with 14 participants from 12 family units to explore the perspectives of parents of children with ASD on the EI message. Thematic analysis was undertaken on the data. Results: Three central themes were constructed following data analysis: (i) parents' initial perceptions of EI following their child's diagnosis with ASD; (ii) the consequences (both positive and negative) of the EI message; and (iii) parents' perspectives on life after EI. The results of this study indicated that parents were acutely aware of the importance of EI, and although this provided parents with hope immediately post‐diagnosis, it also placed pressure on parental decision‐making regarding which intervention approaches to access for their children with ASD. Conclusions: The results of this study highlight the importance of carefully considering how health messages, specifically the importance of EI, are communicated to families of children with ASD. Furthermore, the findings of this study also highlight the need for allied health professionals to communicate openly with parents about the anticipated outcomes of EI programmes.